1978
DOI: 10.1159/000237799
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Granulocytic Leukemia cutis Treated with Hydroxyurea

Abstract: The clinical course of a patient with chronic granulocytic leukemia cutis associated with myeloid metaplasia is described. Cutaneous manifestations of leukemia appeared only at the sites of bone marrow aspiration and vena puncture. Radiotherapy to both spleen and skin and chemotherapy with busulfan failed to control spreading cutaneous lesions. Treatment with hydroxyurea was followed by a marked reduction in spleen size, a decrease in white cell count and healing of the skin lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
1
Order By: Relevance
“…2 The most common indications for hydroxyurea therapy are chronic myeloid leukemia 3 and gastrointestinal malignant melanoma. 4 It has also been used in the management of other myeloproliferative disorders, 5 sickle-cell disease, 6 polycythemia vera, 7 psoriasis, 8 and to inhibit viral replication in human immunodeficiency virus disease. 9 While the drug's mode of action on bone marrow elements is well established, its effects on actively proliferating epithelial cells remain less well described.…”
mentioning
confidence: 99%
“…2 The most common indications for hydroxyurea therapy are chronic myeloid leukemia 3 and gastrointestinal malignant melanoma. 4 It has also been used in the management of other myeloproliferative disorders, 5 sickle-cell disease, 6 polycythemia vera, 7 psoriasis, 8 and to inhibit viral replication in human immunodeficiency virus disease. 9 While the drug's mode of action on bone marrow elements is well established, its effects on actively proliferating epithelial cells remain less well described.…”
mentioning
confidence: 99%
“…[23][24][25][26][27][28] A lichen planuse like and a dermatomyositis-like reaction specific for HU and termed ''HU dermopathy'' by Daoud et al 29 has been reported with long-term therapy. 11,[30][31][32][33][34][35] The association between HU and multiple aggressive squamous cell carcinomas, Bowen's disease, and multiple actinic keratoses in photoexposed areas after a variable latency period has been increasingly reported in the literature. We report 2 additional patients who experienced the sudden onset of multiple actinic keratoses, Bowen's disease, basal cell carcinomas, and squamous cell carcinomas in sun-exposed areas after long-term HU therapy.…”
mentioning
confidence: 99%
“…It has been used in patients with hypereosinophilic syndrome unresponsive to corticosteroids 83 . Also, a patient with chronic granulocytic leukaemia cutis who failed to respond to radiotherapy and busulfan experienced healing of skin lesions with hydroxyurea 84 …”
Section: Other Dermatological Uses Of Hydroxyureamentioning
confidence: 99%